Vascular aging and cardiovascular disease: pathophysiology and measurement in the coronary arteries - Cheng, Daniel C. Y.; Climie, Rachel E.; Shu, Matthew; Grieve, Stuart M.; Kozor, Rebecca; Figtree, Gemma A. (Frontiers in Cardiovascular Medicine, 2023)
Age is a key risk factor for cardiovascular disease, including atherosclerosis. However, pathophysiological disease processes in the arteries are not an inevitable feature of aging. Large cohort studies with arterial phenotyping along with clinical and demographic data are essential to better understand factors related to the susceptibility or resilience to age-related vascular pathophysiology in humans. This review explores the mechanisms by which vascular structure and function alters with age, and how these changes relate to cardiovascular pathophysiology and disease. Features of vascular aging in the coronary arteries have historically been difficult to quantify pre-mortem due to their size and location. However, non-invasive imaging modalities including CT Coronary Angiogram are now being used to assess coronary vascular age, and further advances in imaging analysis such as the CT Fat Attenuation Index will help provide further measurement of features associated with coronary vascular aging. Currently, markers of vascular aging are not used as therapeutic targets in routine clinical practice, but non-pharmacological interventions including aerobic exercise and low salt diet, as well as anti-hypertensives have been demonstrated to reduce arterial stiffness. Advances in imaging technology, both in acquisition and advanced analysis, as well as harmonisation of measurements for researchers across the globe will be invaluable in understanding what constitutes healthy vascular aging and in identifying features of vascular aging that are associated with coronary artery disease and its adverse outcomes. Assessing such images in large cohorts can facilitate improved definitions of resilient and susceptible phenotypes to vascular aging in the coronary arteries. This is a critical step in identifying further risk factors and biomarkers within these groups and driving forward the development of novel therapies aimed at slowing or stopping age-related vascular changes in the coronary arteries.